475 Is left atrial appendage device compression rate a predictor of incomplete occlusion in patients undergoing watchman device implantation?. (8th December 2021) - Magnocavallo, Michele; Rocca, Domenico Giovanni Della; Lavalle, Carlo; Chimenti, Cristina; Carola, Gianni; Mohanty, Sanghamitra; Trivedi, Chintan; Bassiouny, Mohamed; Al-Ahmad, Amin; Burkhardt, David J; Gallinghouse, Joseph G; Sanchez, Javier E; et al.
Abstract: Aims: Transesophageal echocardiography (TEE) is a standard peri-procedural imaging modality in patients undergoing percutaneous left atrial appendage (LAA) occlusion. An accurate device sizing is pivotal to assess stability and achieve successful closure. In this prospective study, we sought to evaluate the correlation between Watchman device compression rates (DCRs) and risk of incomplete LAA occlusion at follow-up in patients undergoing Watchman device implantation. Methods and results: Two-dimensional TEE via a commercially available transducer (Vivid, Philips) was performed during the procedure and within 3 months after the procedure. LAA size, morphology, and DCRs [(original device size—size after deployment)/original device size; %] were assessed in a mid-oesophageal view at 0°, 45°, 90° and 135°, according to company recommendations. Residual leaks ≥ 3 mm were classified as significant. Between 2016 and 2018, 116 patients underwent LAA occlusion with a Watchman device at our institution. The mean age was 74 ± 9 years and 60.4% ( n = 70) were males. The average CHA2DS2-VASc and HAS-BLED scores were 4.7 ± 1.7 and 2.5 ± 1.1, respectively. The final device size was 21 mm in 11 (9.5%) patients, 24 mm in 28 (24.1), 27 mm in 27 (23.3%), 30 mm in 26 (22.4%), and 33 mm in 24 (20.7). At follow-up TEE, 16 (13.8%) patients were found to have a significant (≥3 mm) residual leak. The average DCRs measured at different angles in patients with and without leak were not significantly different (24 ± 8% vs. 26 ± 7% at 0°, P = 0.47; 23 ± 9% vs. 25 ± 7% at 45°, P = 0.58; 23 ± 8% vs. 23 ± 6% at 90°, P = 0.61; 22 ± 8% vs. 21 ± 7% at 135°, P = 0.61). At receiver operating characteristic (ROC) analysis, the areas under the curve to discriminate between patients with/without leak were 0.58, 0.57, 0.55, and 0.46 for DCRs measured at 0°, 45°, 90°, and 135° angles. Conclusions: Peri-procedural assessment of DCRs does not appear to be an accurate method to predict LAA complete occlusion in patients undergoing Watchman device implantation.